ANALISIS PENGARUH WORKING CAPITAL TURNOVER TERHADAP LIKUIDITAS DAN PROFITABILITAS - Minar Savitri, Dhian Andanarini (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
This study aimed to assess the influence of WCT toward profitability and liquidity of manufacturing companies in Indonesia Stock Exchange. The population of this research is every manufacturing company enlisted in the BEI at the year 2009-2012. The samples were obtained by using the purposive sampling method until only 15 companies were qualified as samples. This research used regression analysis method to find out the effect of independent variables, which are wct to the profitability and liquidity of the company.The result of this research shows that the WCT (working capital turnover) has insignificant effect to the profitability and liquidity of manufacturing companies enlisted in the BEI at year 2005-2012.